Point of care testing in family practice: common myths debunked - Howick, J; Bossuyt, P; Cals, J (Oxford University Press, 2016)
Point of care tests (POCTs, also known as ‘near patient’ or ‘bedside’ tests) can save patients and health care practitioners from the trouble and wait of sending samples to the lab. They may also help optimize prescribing decisions (by helping doctors make ‘on the spot’ diagnoses and decisions), reducing referrals, and decreasing costs (fewer patients referred to more expensive specialists).